2016
DOI: 10.1007/s40071-016-0150-1
|View full text |Cite
|
Sign up to set email alerts
|

Surface water quality and deforestation of the Purus river basin, Brazilian Amazon

Abstract: In the last years, deforestation constitutes a threat for the aquatic ecosystems. This paper aims to characterize the water quality of the Purus river in the Brazilian Amazon, and investigate the relations between water quality and deforestation of the Purus river basin over a 9-year period, as well as to quantify the Purus river basin's land cover changes (%) in a 5-year period. Sampling data from upstream to downstream show a decrease in pH-value, dissolved oxygen, electrical conductivity, and total suspende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 9 publications
1
7
0
2
Order By: Relevance
“…More so, the pH values were all within the range of 6.5 to 8.5, as recommended in the World Health Organization guidelines [41]. Similar trends were also reported in the Senqu-Orange River [42], Silva et al [43], Ros-Villamizar et al [44], and Machado et al [45] in streams of the Piracicaba River basin, Brazil. Phiri et al [46] also showed that such slightly lower pH values in effluents from beverage factories as in the current study are due to the nature of the raw materials such as enzymes, lactic acid, benzoic acid, and yeasts that are commonly used in such industries.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…More so, the pH values were all within the range of 6.5 to 8.5, as recommended in the World Health Organization guidelines [41]. Similar trends were also reported in the Senqu-Orange River [42], Silva et al [43], Ros-Villamizar et al [44], and Machado et al [45] in streams of the Piracicaba River basin, Brazil. Phiri et al [46] also showed that such slightly lower pH values in effluents from beverage factories as in the current study are due to the nature of the raw materials such as enzymes, lactic acid, benzoic acid, and yeasts that are commonly used in such industries.…”
Section: Resultssupporting
confidence: 75%
“…The WQI model as adopted by [44] was utilised. The approach makes use of just nine parameters for the computation of the water quality index of a sample of water.…”
Section: Water Quality Index Computation Wqimentioning
confidence: 99%
“…River water pH can also be altered due to terrestrial inputs because most soils in the humid tropics are acidic (e.g., pH = 4.5−6.4; Grip et al 2005). This acidity has both biological and chemical causes: microbial processes (e.g., aerobic oxidation, methanogenesis, sulfate reduction, nitrification) enrich the soil pore water with H + and various forms of oxidized C and N (e.g., CO 2 , CH 4 , NO 3 − ) (Melling et al 2005;Ríos-Villamizar et al 2017), and weathering of parent material may also directly acidify adjacent aquatic systems by reacting with precipitation or moisture. For example, acid sulfate soil (ASS) is widely distributed in tropical regions and is stable under anoxic conditions.…”
Section: Loggingmentioning
confidence: 99%
“…This study was conducted in the Piagaçu‐Purus Sustainable Development Reserve (State of Amazonas, Brazil), which is located south of the confluence of the Solimões and Purus rivers (Figure 1). Lake Ayapuá is situated on the floodplain of the lower Purus River, a whitewater river characterized by high turbidity (20–40 NTU), nearly neutral pH (6–7), high productivity, warm waters, and abundant surface vegetation (Junk et al, 2012; Ríos‐Villamizar et al, 2017). The lake is an oblong, shallow, turbid water body bordered by seasonally flooded lowland forest ( várzea ).…”
Section: Methodsmentioning
confidence: 99%